2019
DOI: 10.1007/s00421-019-04280-w
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity exercise in the evening does not disrupt sleep in endurance runners

Abstract: Purpose To investigate the effect of early evening exercise training at different intensities on nocturnal sleep and cardiac autonomic activity in endurance-trained runners. Methods Eight runners completed three experimental trials in a randomised, counterbalanced order. In the early evening (end of exercise 3.5 h before bedtime), participants performed either: (i) a 1 h high-intensity interval running session (HIGH, 6 × 5 min at 90% VO 2peak interspersed with 5 min recovery); (ii) a 1 h low-intensity running … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
40
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 39 publications
1
40
2
Order By: Relevance
“…In the present study, the nocturnal heart rate slightly decreased in INT, and a significant difference between groups was also observed in the relative change from the control to the training period. Based on these and previous findings, the nocturnal heart rate may react more uniformly and sensitively to high-intensity training, both acutely [ 32 ] and in the long-term [ 19 ], compared to HRV when using nocturnal recordings. Whether this is associated with physiological factors such as changes in plasma volume or cardiac morphology [ 26 ] has yet to be studied.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, the nocturnal heart rate slightly decreased in INT, and a significant difference between groups was also observed in the relative change from the control to the training period. Based on these and previous findings, the nocturnal heart rate may react more uniformly and sensitively to high-intensity training, both acutely [ 32 ] and in the long-term [ 19 ], compared to HRV when using nocturnal recordings. Whether this is associated with physiological factors such as changes in plasma volume or cardiac morphology [ 26 ] has yet to be studied.…”
Section: Discussionmentioning
confidence: 64%
“…A simple nocturnal heart rate reflects somewhat similar aspects of recovery as HRV [ 26 ]. Consequently, the heart rate has been affected acutely most by the intensity of the training [ 27 ], and after high-intensity interval exercise performed in the evening, responses in nocturnal heart rate may be even more severe than in HRV [ 32 ]. On the other hand, after long-term high-intensity training, heart rate may decrease significantly [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…One Note: MPA = moderate physical activity; significant correlations are shown in bold possible explanation could be that participants willingly or unconsciously avoided highly intensive physical activity, because they may expect it to cause negative consequences with regards to their RLS symptoms. However, previous studies of non-RLS patients, have concluded that high-intensity exercise (even when performed in the evening) does not affect sleep [52,53]. Another explanation for the lack of vigorous physical activity among our study population is the use of a high cut-off point to define vigorous physical activity.…”
Section: Discussionmentioning
confidence: 69%
“…Specifically, some studies found that vigorous exercise, especially when performed close to bedtime, may impair sleep behaviour [ 34 ]. However, other studies reported that high-intensity training does not disrupt and may even improve subsequent nocturnal sleep when it is performed in the early evening [ 35 ]. Particularly, our results showed that both types of RT sessions produce the same effect on sleep quality and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…muscle damage or biochemical markers) may have a greater influence on strength performance than sleep quality. However, in most of the previous studies which analysed the effect of exercise on sleep quality, endurance training [ 16 , 31 , 35 ] was performed, or the subjects were older in those cases where they studied the effect of RT [ 37 ]. Therefore, it is necessary to continue analysing the effect of RT on sleep quality because previous studies found that lower sleep quality is related to higher prevalence of sarcopenia [ 38 ] and inadequate sleep impairs maximal muscle strength and muscle growth [ 14 ].…”
Section: Discussionmentioning
confidence: 99%